Our Experience of Optimizing Outcomes in Open Globe Injuries: A Retrospective Case Series - Shilpa Umarani; Pooja Hatti; B N Nanda; Lekha Ravikumar (TNOA Journal of Ophthalmic Science and Research)
Purpose: Ocular injuries frequently result in significant eye-related health issues, often leading to severe and sometimes irreversible vision impairment. This case series aims to highlight the presentation, management and outcomes of various ocular injuries over a 1-month period, emphasizing the necessity for timely and effective intervention. Methods: This case series includes 11 patients with varying degrees of ocular trauma, who presenting to an emergency department over a month. Each case was documented in detail, including patient demographics, mechanism of injury, clinical findings, surgical interventions, and postoperative outcomes. The primary focus was on the initial surgical management and subsequent referral for specialized care when necessary. Results: Case 1 describes a 4-year-old boy who sustained a corneal laceration and cataract, managed with corneal suturing and lens extraction. Case 2 describes a 13-year-old boy who suffered a sclerocorneal tear with iris prolapse, treated with wound exploration and repair. Case 3 described an 18-year-old boy with a thorn injury who underwent corneal repair and anterior vitrectomy. Cases 4-11 include various injuries, such as full-thickness corneal tears, hyphema, conjunctival lacerations, and lens dislocation, each managed with appropriate surgical intervention and postoperative care. The cases underscore the complexity of ocular trauma management and the critical need for prompt, skilled intervention. The variability in injury mechanisms and severity highlights the importance of tailored surgical approaches and the role of early referral to specialized care for optimal outcomes. Conclusion: Ocular trauma presents diverse challenges requiring prompt and effective management to prevent long-term visual impairment. This case series emphasizes the importance of comprehensive emergency care and specialized follow-up to address the multifaceted nature of ocular injuries.